Influence of the degree of coal metamorphism on characteristics and conditions of ignition of coal-water fuel drops; Thermophysics and Aeromechanics; Vol. 25, iss. 5 - Salomatov V. V. Vladimir Vasiljevich (2018, 2018)
Title screen